Analisis Kesenian Rudat “Gaya Cigadogan” di Kampung Cigadog Desa Cigadog Kecamatan Leuwisari - Yeni Handayani; Asep Wasta; Wan Ridwan Husen (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This research aims to analyze one of the traditional arts, Rudat. The traditional art that still exists in West Java is Rudat art in Kampung Cigadog, Cigadog Village, Leuwisari District. Rudat art is vocal art accompanied by tarebang and kendang bajidor percussion, as well as silat movements and chanting of sholawat. The presentation and performance structure of Rudat art in Cigadog involve several elements, including movements, dancers, accompanying music, and costumes. The Rudat performance